Pojok Literasi Sebagai Upaya Peningkatan Minat Baca Siswa SDN Menampu 04 Kabupaten Jember - Eva Rosdiana; Rizky Nirmala Kusumaningtyas; Putu Tessa Fadhila; Fandyka Yufriza Ali; Annisa Lutfi Alwi (Indonesian Journal Publisher, 2022)
Interest in reading should be instilled from an early age, especially at school age. The fear of students coming to the library and the availability of books are internal and external factors. Both of these factors should be addressed properly. Thus, in this service, a literacy corner and book additions were held at SDN Menampu 04 Jember. There are several stages in the implementation of this service including 1) survey and observation, 2) planning, 3) implementation and 4) evaluation. A literacy corner is held in each class. In addition, 123 books, both fiction and non-fiction, were added. The books added also use Indonesian, English, and Regional languages. The publishers and authors of the added books also vary. So that it can increase reading interest from SDN Menampu 04 Jember. Procurement of literacy corners equipped with additional books can increase the reading interest of SDN Menampu 04 students. This is due to the existence of literacy corners in each class, as well as the many variations of books in SDN Menampu 04.